Entre tempos, contratempos e passatempos: educação infantil em jornada de tempo integral - Sabatini, Viviane Menezes (2021)
Early childhood education in the country has been offered in a polarized way between schooling practices for part-time preschools and welfare practices for day-care centers on a full-time basis. However, since the incorporation of this last stage into the education system, there has been a transformation in the provision of care due to pressure from social movements. In addition, the very conception of a child, when changing historically, created the need to formulate educational policies that advocate the balance between caring and educating - two pillars of the triad that is completed with playing - as well as advances in studies on child development demonstrated the relevance of ensuring the quality of the experiences provided to young children in children's equipment, whether part-time or full-time. This research arises from the perception that the offer of full-time work, characterized by the child's long stay within the school space, demands the elaboration of quality educational policies so that, during the entire period spent at school, comprehensive formation is offered for this audience. As a problem, he questions whether, in extending the time spent in kindergarten, children would be guaranteed to play, educate and care, thus addressing their limits and possibilities. In this dimension, the general objective of the study is to analyze the supply and attendance of early childhood education in the school system of Rio Claro, a municipality in the interior of São Paulo; its specific objectives sought to characterize this reality in the researched education school system, as well as to examine the conceptions of children, childhood and early childhood education present in the official texts for education in the city where the research was located. As methodological designs, the research was undertaken through bibliographic research, document analysis and semi-structured interviews with the management team of the municipal education department. The results of the study showed that the main challenges and difficulties for the development of full-time educational work are related to the fragmentation between the care-to-educate functions and the persistence of care concepts still present in educational practices in early childhood education that work full time, that when they understand the role of the school as a place for childcare, they offer basic care and a hobby, thus compromising the comprehensive education necessary for childhood. Finally, the research points out that, although the legislation has advanced at the federal, state and municipal levels, there is still a need for improvement so that the integral education effectively occurs in the full-time day in Brazilian early childhood education.